A long-term evaluation of the stage of change approach and compensable injury outcomes – a cluster-randomised trial. Issue 5 (4th May 2017) - Rothmore, Paul; Aylward, Paul; Gray, Jodi; Karnon, Jonathan
Abstract: This study investigated the long-term injury outcomes for workers in companies from a range of industries which had been randomly allocated to receive ergonomics interventions tailored according to the stage of change (SOC) approach or standard ergonomics advice. Differences in compensable injury outcomes between the groups were analysed using logistic regression models. Questionnaire results from face-to-face interviews to assess musculoskeletal pain and discomfort (MSPD), job satisfaction and other factors were also analysed. Although not significant at the 0.05 level, after adjusting for workgroup clustering, workers in receipt of tailored advice were 55% (OR = 0.45, 95% CI = 0.19–1.08) less likely to report a compensable injury than those in receipt of standard ergonomics advice. Workload, job satisfaction and MSPD were significantly correlated with injury outcomes. The observed outcomes support the potential value of the SOC approach, as well as highlighting the need to consider workload, job satisfaction and MSPD when planning injury prevention programmes. Practitioner Summary : This study investigated compensable injury outcomes for workers who had received ergonomics advice tailored according to the stage of change (SOC) approach compared with standard ergonomics advice. The results support the potential value of the SOC approach and highlight the need to consider workload, job satisfaction and musculoskeletal pain and discomfort when planning injury prevention interventions.